Pelatihan Pembuatan Media Augmented Reality Menggunakan Aplikasi Assemblr untuk Mengembangkan Kompetensi Digital Guru PAUD - Rizka Aisyah (Jurnal Pengabdian Pendidikan, 2025)
In the era of Society 5.0, Kindergarten teachers need to have strong digital competencies where teachers are more innovative and adaptive in learning and also utilize digital technology to improve the quality of early childhood education. Training in making Augmented Reality learning media using Assemblr to improve digital competency in 28 Kindergarten teachers in Bojonegoro. This activity is carried out in 3 stages, namely pre-training, training and post-training. The pre-training stage is the preparation stage, such as organizing events, taking care of permits, preparing materials and questionnaires. The Implementation Stage or the core of the training activity, begins with the provision of pre-training questionnaires, material, and training in making Augmented Reality media using Assemblr. The post-training stage (evaluation) is the provision of post-training questionnaires, making AR projects, and presenting the results of Augmented Reality media. The results of this training show that 100% of teachers are interested in making Augmented Reality media and 100% of teachers are interested in implementing it in early childhood. The level of satisfaction of Kindergarten teachers with Augmented Reality media material is 25% quite satisfied, 25% satisfied, and 50% very satisfied. Based on these data, it can be concluded that Augmented Reality media creation training can improve the digital competence of Kindergarten teachers and can develop digital learning in early childhood Di era Society 5.0 guru PAUD perlu memiliki kompetensi digital yang kuat dimana guru lebih inovatif dan adaptif dalam pembelajaran juga memanfaatkan teknologi digital untuk meningkatkan kualitas pendidikan anak usia dini. Pelatihan pembuatan media pembelajaran Augmented Reality menggunakan Assemblr untuk meningkatkan kompetensi digital pada 28 guru PAUD di Kabupaten Bojonegoro. Kegiatan ini dilaksanakan dalam 3 tahap yakni pra pelatihan, pelatihan dan pasca pelatihan. Tahap pra pelatihan yakni tahap persiapan, seperti penyusunan acara, mengurus perizinan, mempersiapkan materi dan kuesioner. Tahap Pelaksanaan atau inti kegiatan pelatihan, dimulai dengan pemberian kuesioner pra pelatihan, pematerian, serta pelatihan pembuatan media Augmented Reality menggunakan Assemblr. Tahap pasca pelatihan (evaluasi) yaitu pemberian kuesioner pasca pelatihan, pembuatan proyek AR, serta presentasi hasil media Augmented Reality. Hasil pelatihan ini menunjukkan bahwa 100% guru berminat untuk membuat media Augmented Reality serta 100% guru berminat untuk mengimplementasikan pada anak usia dini. Tingkat kepuasan guru PAUD terhadap materi media Augmented Reality sebesar 25% cukup puas, 25% puas, dan 50% sangat puas. Berdasarkan data tersebut dapat disimpulkan bahwa pelatihan pembuatan media Augmented Reality dapat meningkatkan kompetensi digital guru PAUD serta dapat mengembangkan pembelajaran digital pada anak usia dini.